A REVIEW OF THE NON-DEMARCATION BORDER COOPERATION BETWEEN INDONESIA AND MALAYSIA - Michelle Viandy Huang (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2019)
Indonesia and Malaysia have established cooperation on various aspects of the border regions for decades. The two countries have ratified the 1984 Security Arrangement Treaty, where the General Border Committee (“GBC”) is established to contend the security aspect of the border areas. The GBC also formed a Social Economic Committee of Indonesia and Malaysia, which is called the SOSEKMALINDO, focusing on the social and economic aspects of the border. Meanwhile, there has been the 1970 Agreement on Border Trade (“BTA”) that governs the movement of goods in and out of the border and maintain the border’s economy. As time goes by, the border cooperation between the two countries has developed, resulting the need to meet the new challenges in terms of border security. While the governments have been emphasizing its focus on economic cooperation, the security challenges are neglected. Hence, this paper provides an analysis on the urgency to reform the 1984 Security Arrangement Treaty due to the overlapping function between the GBC and the BTA.BAHASA INDONESIA ABSTRAK: Indonesia dan Malaysia telah menjalin kerja sama dalam berbagai aspek wilayah perbatasan selama beberapa dekade. Misalnya, kedua negara telah meratifikasi Security Arrangement Treaty 1984, di mana General Border Committee ("GBC") dibentuk untuk memperjuangkan aspek keamanan wilayah perbatasan. GBC juga membentuk Komite Sosial Ekonomi Indonesia dan Malaysia, yang disebut SOSEKMALINDO. Komite ini berfokus pada aspek sosial dan ekonomi perbatasan. Sementara itu, telah ada Perjanjian 1970 tentang Perdagangan Perbatasan (“BTA”) yang mengatur pergerakan barang masuk dan keluar dari perbatasan dan menjaga ekonomi perbatasan. Seiring berjalannya waktu, kerja sama perbatasan antara kedua negara telah berkembang, menghasilkan kebutuhan untuk memenuhi tantangan baru dalam hal keamanan perbatasan. Sementara pemerintah kedua negara menaruh fokusnya dalam kerja sama ekonomi, masalah keamanan masih diabaikan. Oleh karena itu, jurnal ini memberikan analisis tentang urgensi untuk mereformasi Security Arrangement Treaty 1984 atas dasar fungsi GBC dan BTA yang saling tumpang tindih.